Fully state-selected VMI study of the near-threshold photodissociation of NO(2): variation of the angular anisotropy parameter. - Matthews, S; Willitsch, S; Softley, T (2007)
Velocity-map ion imaging (VMI) has been used to study the angular distribution of the NO fragment generated in the photodissociation of NO(2) at a variety of photolysis wavelengths. Images were recorded for the channels NO (2)Pi(1/2) (v = 0, J= 3/2, 11/2 and 21/2) + O ((3)P(2,1)), for excitation energies ranging from the onset (E(avl)/hc = 0 cm(-1)) to E(avl)/hc approximately 900 cm(-1). The angular anisotropy parameter beta was obtained as a function of available energy. Photofragment multiphoton ionization (PHOMPI) spectra were also recorded in the energy range E(avl)/hc = 0-300 cm(-1) for each of these channels. Large fluctuations of beta as a function of E(avl) were found in all observed dissociation channels. These variations are discussed in terms of the lifetimes of the originally photoexcited overlapping resonances in the A(2)B(2) state of NO(2), the dynamics of which are strongly influenced by nonadiabatic coupling with the X[combining tilde](2)A(1) state. The potential use of this photolysis process for production of cold oxygen atoms is discussed.